Polycystic ovary syndrome - Molina Navia, Lucas (2015)
Since 1935 it is recognized as a clinical entity polycystic ovary syndrome; It was from its original description that the therapeutic value of the wedge resection of the ovaries was noted that Stain and Leventhal performed with diagnostic intention. In recent years it has made significant progress in the understanding of the pathophysiology of this syndrome, thanks to advances in the study of nature, and control secretion of ovarian hormones.